Ethical use of off-label disease-modifying therapies for multiple sclerosis. (August 2021) - Laurson-Doube, Joanna; Rijke, Nick; Helme, Anne; Baneke, Peer; Banwell, Brenda; Viswanathan, Shanthi; Hemmer, Bernhard; Yamout, Bassem
Background: Off-label disease-modifying therapies (DMTs) for multiple sclerosis (MS) are used in at least 89 countries. There is a need for structured and transparent evidence-based guidelines to support clinical decision-making, pharmaceutical policies and reimbursement decisions for off-label DMTs. Objectives/Results: The authors put forward general principles for the ethical use of off-label DMTs for treating MS and a process to assess existing evidence and develop recommendations for their use. Conclusion: The principles and process are endorsed by the World Federation of Neurology (WFN), American Academy of Neurology (AAN), European Academy of Neurology (EAN), Americas Committee for Treatment and Research in Multiple Sclerosis (ACTRIMS), European Committee for Treatment and Research in Multiple Sclerosis (ECTRIMS), Middle-East North Africa Committee for Treatment and Research in Multiple Sclerosis (MENACTRIMS) and Pan-Asian Committee for Treatment and Research in Multiple Sclerosis (PACTRIMS), and we have regularly consulted with the Brain Health Unit, Mental Health and Substance Use Department at the World Health Organization (WHO).